PENINGKATAN PROFESIONALISME GURU-GURU BAHASA INGGRIS SMA KABUPATEN JAYAPURA - Budi Rahayu; Ruth N. Nancy Wompere (JURNAL PENGABDIAN PAPUA, 2019)
Professionalism in taching has become the target of teachers in Indonesia to be achieved. For this reason, this community service program has been conducted. The purpose of this activity is to improve professionalism of Senior High School English teachers in the regency of Jayapura, especially in mastering text types. The method used was interviews and group discussion. This activity has resulted in the improvement of the teachers’ more understanding on text types so they can have enough knowledge to teach their students confidently. This program has also revealed some problems the schools have.Keywords: English teachers, Professionalism, Text Types